Estudio sobre el comportamiento de compra en carne vacuna de población de la región pampeana - Kent, Federico; Soteras, Trinidad; Maitia, Carolina Soledad; Leiton, Héctor Rafael; Porta Siota, Fernando; Volpi Lagreca, Gabriela; Hurtado, Ariel Walter; Denoya, Gabriela Inés (Asociación Argentina de Producción Animal (AAPA), 2024)
Ponencia y póster